Raising Public Legal Awareness in the Digital Age: Global Practices and Indonesia’s Path Forward - Serah, Yenny Aman; Jha, Gautam Kumar; Purwanto; Sirait, Resmaya Agnesia Mutiara; Astono, Agustinus (Universitas Negeri Semarang, 2025)
This article explores the utilization of digital technology to enhance public legal awareness from a comparative global perspective. In the digital era, technology has become a significant tool for expanding access to legal information and empowering individuals to understand their legal rights and obligations. This study analyzes various global practices, including digital initiatives such as law-based mobile applications, e-learning platforms, social media-based legal awareness campaigns, and online legal aid systems. Furthermore, the article evaluates the necessary legal reforms to effectively support the use of digital technology in legal contexts, with a focus on Indonesia. By comparing approaches in countries such as the United States, the United Kingdom, and Scandinavian nations, this research provides recommendations to strengthen inclusive and equitable digital legal awareness strategies. The article underscores the importance of technological innovation in fostering a legally informed society and supporting legal transformation in the digital age.